Dual‐Vibration‐Assisted Charge Transport Through Hexabenzocoronene in Single‐Molecule Junctions - Miao Zhang; Boyu Wang; Hongxing Jia; Xinmiao Xie; Jie Hao; Li Zhou; Pingwu Du; Jinying Wang; Chuancheng Jia; Xuefeng Guo (Advanced Science)
Abstract Gaining deep understanding and effective regulation of the charge transport mechanism within molecular junctions is essential for the development of electronic devices. In this work, a series of hexabenzocoronene‐based single‐molecule junctions are successfully constructed, and their temperature‐dependent charge transport properties are studied. It is found that rotational vibrations of both benzene and hexabenzocoronene rings are sequentially excited as the temperature increases, and the electron‐vibration coupling enhances charge tunneling. In addition, the transition temperature between distinct vibration‐assisted tunneling modes and the activation energies show strong correlations with the molecular vibration frequency and molecular length. This study unveils the distinct dual‐vibration‐assisted molecular tunneling mechanism, significantly enhancing the ability to precisely control molecular charge transport and develop functional molecular devices.